The 2015 Paris Terrorist Attacks: An Assessment - Yeo, Weimeng (2016)
The suicide armed attacks in Paris on 13 November 2015 were unprecedented in magnitude and scale. It has exposed France’s vulnerability to political armed violence and has alerted the rest of Europe to the jihadist threat within their domain.